Download presentation

Presentation is loading. Please wait.

Published byTracy Denis O’Connor’ Modified over 5 years ago

1
**OBJ: To solve a quadratic equation by factoring**

3.5 Quadratic Equations OBJ: To solve a quadratic equation by factoring

2
**DEF: Standard form of a quadratic equation**

ax2 + bx + c = 0 NOTE: Each equation contains a polynomial of the second degree.

3
**DEF: Zero – product property**

If mn = 0, then m = 0 or n = 0 or both = 0 NOTE: Solve some quadratic equations by: Writing equation in standard form Factoring Setting each factor equal to 0

4
**EX: 5 c 2 + 7c – 6 = 0 3 5 2 2 1 3 -3 3 2 +10 (5c – 3)(c + 2) = 0**

-3 3 2 +10 (5c – 3)(c + 2) = 0 c = 3/5, -2

5
EX: 7t = 20 – 3 t 2 3 t 2 + 7t – 20 = 0 -5 5 4 +12 (3t – 5)(t + 4) = 0 t = 5/3, -4

6
EX: 36 = 25 x 2 25 x 2 – 36 = 0 (5x – 6)(5x + 6) = 0 x = ± 6/5

7
EX: –2 x 2 = 5x 2 x 2 + 5x = 0 x(2x + 5) = 0 x = 0, - 5/2

8
**EX: 7 n 2 + 14n – 56 = 0 7 (n 2 + 2n – 8) = 0 7 (n + 4)(n – 2) = 0**

9
EX: y 4 – 5 y = 0 (y 2 – 4)(y 2 – 1) = 0 (y – 2)(y + 2)(y – 1)(y + 1) = 0 Y = ± 2, ± 1

10
EX: y 4 – 10 y = 0 (y 2 – 9)(y 2 – 1) = 0 (y – 3)(y + 3)(y – 1)(y + 1) = 0 Y = ± 3, ± 1

11
**EX: y 4 = 20 – y 2 y 4 + y 2 – 20 = 0 (y 2 + 5)(y 2 – 4) = 0**

Y = ± i√ 5, ± 2

12
**EX: y 4 = 12 + y 2 y 4 – y 2 – 12 = 0 (y 2 – 4)(y 2 + 3) = 0**

Y = ± 2, ± i√ 3

13
6.1 Square Roots OBJ: To solve a quadratic equation by using the definition of square root DEF: Square root If x 2 = k, then x = ±√k, for k ≥ 0

14
EX: 6 y 2 – 20 = 8 – y 2 7y 2 = 28 y 2 = 4 y = ± 2

15
EX: 3 n = 7 n 2 – 35 44 = 4n 2 11 = n 2 ±√11 = n

16
7.3 The Quadratic Formula OBJ: To solve a quadratic equation by using the quadratic formula DEF: The quadratic formula x = -b ± √b2 – 4ac 2a

17
**EX: 4 x 2 – 7x + 2 = 0 x = -(-7) ± √(-7)2 – 4(4)(2) 2(4)**

= 7 ± √49 – 32 8 = 7 ± √17

18
**EX: 9 x 2 = 12x – 1 9 x 2 – 12x + 1 = 0 x = -(-12)±√(-12)2 – 4(9)(1)**

2(9) = 12 ± √144 – 36 18 = 12 ± √108 = 12 ± 6√3 = 12 ± 6√3 18 = 6(2 ± √3) 3 = 2 ± √3

19
EX: 6 x 2 + 5x = 0 x(6x + 5) = 0 x = 0, -5/6

20
EX 8: 72 – x 2 = 0 x 2 = 72 x = ± 6√2

21
**8.3 Equations With Imaginary Number Solutions**

OBJ: To solve an equation whose solutions are imaginary

22
**EX: 2 x 2 + 7 = 6x 2 x 2 – 6x + 7 = 0 x = -(-6)±√(-6)2 – 4(2)(7)**

2(2) = 6 ± √36 – 56 4 = 6 ± √-20 = 6 ± 2i√5 = 2(3 ± i√5) 4 2 = 3 ± i√5

23
**EX: 27 – 6 y 2 = y 4 y 4 + 6 y 2 – 27 = 0 (y 2 + 9)(y 2 – 3) = 0**

y = ± 3i, ± √3

Similar presentations

© 2021 SlidePlayer.com Inc.

All rights reserved.

To make this website work, we log user data and share it with processors. To use this website, you must agree to our Privacy Policy, including cookie policy.

Ads by Google